Computer Language Effciency via Data Envelopment Analysis. (22nd November 2011) - Ellero, Andrea; Pellegrini, Paola
Abstract : The selection of the computer language to adopt is usually driven by intuition and expertise, since it is very diffcult to compare languages taking into account all their characteristics. In this paper, we analyze the effciency of programming languages through Data Envelopment Analysis. We collected the input data from The Computer Language Benchmarks Game : we consider a large set of languages in terms of computational time, memory usage, and source code size. Various benchmark problems are tackled. We analyze the results first of all considering programming languages individually. Then, we evaluate families of them sharing some characteristics, for example, being compiled or interpreted.